Collegiate Recovery Programs: The Integrated Behavioral Health Model. Issue 2 (3rd April 2018) - Ashford, Robert D.; Brown, Austin M.; Curtis, Brenda
ABSTRACT: Campus-based recovery programs have been shown to support students in recovery from substance use disorders, as well as mental health disorders. However, this support has been historically delivered in isolation. This study highlights preliminary outcomes from a novel collegiate recovery program, one that uses a model of recovery with integrated support services for students in recovery from substance use or mental health disorders, or co-occurring behavioral health disorders. Similar to traditional collegiate recovery programs, beneficial services of the integrated program were most often related to peer-based services. Outcomes were also similar, with students in recovery having higher than average Grade Point Average (M = 3.68, SD = .34) and lengths of recovery time (M = 3.69, SD = 2.87 [years]).